ANALISIS KRITIS KORELASI ASESMEN AUTENTIK DALAM PEMBELAJARAN - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The UNESCO report has established four pillars of education as the basis for educationin the global era: (1) learning to know, learning to learn, (2) learning to do so, learners usingtheir knowledge to develop skills, (3) learning, while learners use their knowledge and skills tolive, and (4) learning to live together, mutual learning mutual understanding requires mutualrespect for human beings. The follow-up of the educational foundation is the emergence oforientation towards the establishment of competence in accordance with the demands of the realworld. Field observations show that the scoring system used by teachers in general is a paperand pencil test because it is considered practical enough in the sense that it does not require alot of energy, cost and time. Good judgment refers to an evaluation of student performance as awhole and produces assumptions about learning and production of the wise, including qualityor achievement of tasks such as tests, projects, reports and examinations. This is offered by theAuthentic Assessment because authentic assessment is the usual learning standard, whether theassessment is standard or alternative, must include theory, technique, practice, application andoutcome. Authentic assessment in accordance with the UNESCO report. There is a CriticalAccess link as the backbone of the competency-based curriculum. And there is a relationshipbetween applying authentic assessments to the curriculum. There are several challenges thattend to occur when the application of authentic assessment is done in learning.